Rice Bran Stabilization Using Autoclave and Optimization of Crude Rice Bran Oil Recovery Using Ultrasound-Assisted Extraction - Dodyk Pranowo; Tsamara Dhany Savira; Sukardi (BioResources, 2023)
This research aimed to stabilize rice bran to reduce enzymatic reactions and optimize rice bran oil extraction using ultrasound-assisted extraction (UAE). The optimization was performed using response surface methodology (RSM). The results showed that rice bran oil has three primary fatty acids (oleic, linoleic, palmitic). Stabilization of rice bran using an autoclave (121 °C) for 10 min was recommended, with oil yield (14.2%), free fatty acid/FFA (0.41%), and gamma oryzanol (16.1 ppm). The storage significantly affected oil yield and gamma oryzanol but not FFA (p>0.05). The untreated and stabilized rice bran FFA during 18-day storage ranged from 1.33 to 5.73% and 0.41 to 1.12%. This confirmed that stabilization could inactivate lipase enzymes by reducing FFA. The optimization showed that the linear model best explained oil yield, total phenol content (TPC), and antioxidant activity (IC50), while the 2FI model was best fitted for gamma oryzanol. The optimal condition was found for UAE extraction at an amplitude of 90% and a time of 30 min. Verifying optimal conditions resulted in oil yield (13.6%), TPC (44.8 mg GAE/g), IC50 (207.2 ppm), and gamma oryzanol (15.8 ppm). Further in-depth studies are required to investigate using green solvents in the UAE and gamma oryzanol purification.